PENDIDIKAN ISLAM INTERDISIPLINER - Sitti Fatimah (PT. Saha Kreasi Indonesia, 2025)
An interdisciplinary approach to Islamic education offers a path to integrating Islamic values with general sciences to address the complexity of social, technological, and ethical problems in the modern era. Interdisciplinary Islamic education is a comprehensive approach that integrates various disciplines in understanding, developing, and applying Islamic educational values. This approach emerged in response to the complexity of modern educational problems that can no longer be solved by a single field of study. Interdisciplinarity serves to enrich the perspective of Islamic education by integrating social sciences, humanities, psychology, philosophy, and even natural sciences. This article examines the concept, theoretical and philosophical foundations, scope, implementation models, benefits, and challenges of interdisciplinary Islamic education, as well as its implications for curriculum and learning practices. Policy recommendations are provided for curriculum development, teacher training, and follow-up research. Building Islamic education based on religious moderation through interdisciplinary Islamic studies is an inseparable link. Using library research, this paper is born from in-depth reflection based on the literature review obtained. To realize the interdisciplinary Islamic studies movement and strengthen Islamic education based on religious moderation, it is necessary to take firm steps, with encouragement and cooperation from various parties. The method used is a literature review of a number of recent publications. The results of this study indicate that interdisciplinary Islamic education can produce educational formulations that are more relevant, adaptive, and responsive to the demands of the times.